Experiences of Altruism in the Therapeutic Relationship: Perspectives of Counselors‐in‐Training and Their Clients. Issue 2 (7th October 2019) - Flasch, Paulina; Limberg‐Ohrt, Dodie; Fox, Jesse; Ohrt, Jonathan H.; Crunk, Elizabeth; Robinson, Edward
Abstract : The purpose of this phenomenological investigation was to explore experiences of altruism in the therapeutic relationship to better understand how counselors‐in‐training (CITs) and their clients mutually perceived the construct in sessions. Findings from interviews with clients ( n = 14) included emotional–relational characteristics and cognitive–behavioral aspects of altruism by their counselors. Findings from interviews with CITs ( n = 10) included explorations of the role of altruism in counseling, overall experiences of altruism in counseling sessions, and experiences of altruism with specific clients. Implications for practice and research are discussed.